Islam, Keindonesiaan dan Bhinneka Tunggal Ika - Elly Malihah (Universitas Nasional, 2020)
The dialogue of Pancasila as the foundation of the state should be a final. The problem is, why must Pancasila be the foundation of the state of the archipelagic state of the Indonesia republic? A long discussion was going on during formulating it what would be the foundation of the independence's Indonesia in the meeting of investigating committee for preparatory work for independence so that the birth of Pancasila as the foundation of the state has been the right decision and visible. Pancasila as the foundation of Indonesia's independence has been tested sociologically because of Indonesia as a multicultural country contains the diversity of race, culture, and religion. This diversity may possibly appear a conflict, that is why it takes comprehension to live together in the bound of maintaining this diversity. Islam as the majority religion roles significantly in the birth of Pancasila as the foundation of the state. Nowadays, is it still required to debate between Islam, Indonesia, and the unity in diversity. This article views how sociology's point of view about this issue, the writer tries to expose is based on the writer's perception and literature study. The result of this study shows that the practice of Islam influences the tradition of Indonesian; the source of Pancasila's value came from religious teaching and practice in society. The phrase of Bhinneka Tunggal Ika is the foundation and vision in the diversity.